Tales out of School - Nwankwo Nkem (African Universities Press, 1963)
Bayo goes to secondary school and in his first term experiences a class rebellion and a challenge to the school football team. Bayo's adventure continues in More Tales out of School.
Keywords: Juvenile Fiction / Adventure / Experience